Persepsi Orang Tua Terhadap Penentuan Sekolah Bilingual Jenjang Paud Dan SD Pada Masa Pandemi Covid-19 - Heru Pratikno (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
This study aims to determine how much parents want to enroll their children in bilingual schools at the PAUD and SD levels during the current pandemic. The data collection method used in this study was a questionnaire given to parents. Then, the data will be analyzed using descriptive quantitative methods. The results of this study indicate that most parents keep their children enrolled in school, especially at the elementary school level. The schools he was aiming for were varied, ranging from bilingual schools, public schools, or Islamic schools. However, there are also parents who postpone their children to go to school, both at the PAUD and SD levels. The reason is that they are worried about their children's health because they are still in the atmosphere of the COVID-19 pandemic.Keywords: Parents' Perceptions, Determination of Bilingual Schools, in the Age of COVID-19. Abstrak Penelitian ini bertujuan mengetahui seberapa besar keinginan orang tua memasukkan anak mereka ke sekolah bilingual jenjang PAUD dan SD pada masa pandemi seperti sekarang ini. Metode pengumpulan data yang digunakan dalam penelitian ini adalah kuesioner yang diberikan kepada orang tua. Kemudian, data tersebut akan dianalisis dengan menggunakan metode kuantitatif deskriptif. Hasil penelitian ini menunjukkan bahwa sebagian besar orang tua tetap memasukkan anak mereka ke sekolah, terutama di jenjang SD. Sekolah yang ditujunya pun beragam, mulai dari sekolah bilingual, sekolah negeri, atau sekolah Islam. Namun, ada pula orang tua yang menunda anaknya untuk masuk sekolah, baik jenjang PAUD maupun SD. Alasannya adalah mereka khawatir akan kesehatan anaknya karena masih dalam suasana pandemi COVID-19.Kata Kunci: : Persepsi Orang Tua, Penentuan Sekolah Bilingual, di Masa COVID-19